Geographic distribution and coverage of pediatric ophthalmologists in the United States - Franco, Jovany J.; Shapiro, Jeremy N.; Johnson-Griggs, Mikaelah A.; Mian, Shahzad I. (Journal of AAPOS, 2025)
The United States faces a persistent shortage of pediatric ophthalmologists (POs). Improved characterization of the geographic distribution and reach of providers is needed to inform health policy, trainee recruitment, and care delivery efforts. We use drive time–based service area analysis to characterize the geographic coverage of POs in the United States and show that 1 in 7 American children live outside 60 minutes of PO care, with reduced access associated with several demographic variables.